Rekomendasi Pemupukan NPK pada Tanaman Kakao (Theobroma Cacao) di Desa Metun Sajau Kecamatan Tanjung Palas Timur, Kabupaten Bulungan, Provinsi Kalimantan Utara: Recommendations For NPK Fertilization on Cocoa (Theobroma Cacao) Plants in Metun Sajau Village, East Tanjung Palas Sub-District, Bulungan District, North Kalimantan Province (Jurnal Ecosolum, 2022)
Nutrients are the most important thing in plant growth, where one of the nutrients in the soil is nitrogen, phosphorus, and potassium. Without nutrients in the soil, the growth process in plants will also experience obstacles. This study aims to determine the percentage of NPK nutrient content in the soil and to provide fertilizer recommendations for nutrient-deficient soils in Metun Sajau Village, Bulungan, North Kalimantan. This research method uses a random sampling technique based on randomization rules, namely, there is no limit to the number of soil samples to be selected by using GPS to determine the sampling point and by using a mineral drill to take soil samples at each location. All sampling points have the same probability and are independent of each other. Soil sampling will be carried out by taking the top layer of topsoil with a depth of about 0-30 cm by taking 12 soil sample points. And with the provisions of 0.5-3 Ha / 3 points of soil samples. Then the soil samples that have been taken are composited and then labeled. Soil samples taken from the field will then be analyzed and tested in the University of Borneo Tarakan soil laboratory for analysis. The results showed that the recommended fertilization recommendations were Urea, SP-36, KCL, and 15-10-12 compound fertilizer with doses according to plant age and class suitability conditions on the land.
Keywords: Recommendations; Nitrogen; Phosphor; Potassium; Fertilization